2018
DOI: 10.1021/acsomega.8b00205
|View full text |Cite
|
Sign up to set email alerts
|

NHC Pd(II) and Ag(I) Complexes: Synthesis, Structure, and Catalytic Activity in Three Types of C–C Coupling Reactions

Abstract: Four bis-benzimidazolium salts, 1,4-bis[1′-( N -R-benzimidazoliumyl)methyl]-2,3,5,6-tetramethylbenzene 2X – ( L 1 H 2 ·(PF 6 ) 2 : R = ethyl, X = PF 6 ; L 2 H 2 ·Br 2 : R = picolyl, X = Br; L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 120 publications
2
13
0
Order By: Relevance
“…The signal for the carbene carbon in NHC Ag(I) complex AgL5 is invisible. This phenomenon has been reported also for some other Ag(I) carbene complexes, which may result from the fluxional behavior of NHC Ag(I) complexes [18][19][20][21]. ESI-MS spectrum gives a multiplicity of signals between 483.0 and 485.8 Dalton attributable to [C 18 H 18 AgBrN 2 O 2 + H + ] + , due to two silver (107 and 109) and two bromine (79 and 81) isotopes with a very similar relative abundance.…”
Section: Synthesis Of N-[4-(hydroxymethyl)phenyl]-n'-[(2-hydroxy-2-phenyl)ethyl]-imidazole-2ylidene]-silver(i)bromide] (Agl5)supporting
confidence: 74%
“…The signal for the carbene carbon in NHC Ag(I) complex AgL5 is invisible. This phenomenon has been reported also for some other Ag(I) carbene complexes, which may result from the fluxional behavior of NHC Ag(I) complexes [18][19][20][21]. ESI-MS spectrum gives a multiplicity of signals between 483.0 and 485.8 Dalton attributable to [C 18 H 18 AgBrN 2 O 2 + H + ] + , due to two silver (107 and 109) and two bromine (79 and 81) isotopes with a very similar relative abundance.…”
Section: Synthesis Of N-[4-(hydroxymethyl)phenyl]-n'-[(2-hydroxy-2-phenyl)ethyl]-imidazole-2ylidene]-silver(i)bromide] (Agl5)supporting
confidence: 74%
“…Thus TbPo‐Pd(II) was attempted as catalyst in the Suzuki–Miyaura coupling reaction, and amazing effect was observed. First, the previous studies reported that the influences of solvents and bases were significant for the Suzuki–Miyaura coupling reaction . So, the promotional effect between solvents and TbPo‐Pd(II) was initially investigated with bromobenzene as the typical substrate, during which K 3 PO 4 ·3H 2 O was applied as the base, and the results are summarized in Table (entries 1–10).…”
Section: Resultsmentioning
confidence: 99%
“…(E)-1-styrylnaphthalene (10 b): [46] White solid; Yield: 95 %; 68-70°C; [45] Yellow solid; Yield: 92 %; m.p 112-114°C; 1 H NMR (500 MHz, CDCl 3 ) δ 10.02 (s, 1H), 7.90 (d, J = 7.7 Hz, 2H), 7.68 (d, J = 7.7 Hz, 2H), 7.57 (d, J = 7.4 Hz, 2H), 7.41 (t, J = 7.3 Hz, 2H), 7.34 (t, J = 7.2 Hz, 1H), 7.27 (s, 1H), 7.17 (d, J = 16.3 Hz, 1H). 13 (E)-1-(4-styrylphenyl)ethan-1-one (10 d): [45] Yellow solid; Yield: 93 %; m.p 138-141°C; 1 H NMR (400 MHz, CDCl 3 ) δ 7.94 (d, J = 8.3 Hz, 2H), 7.57 (d, J = 8.3 Hz, 2H), 7.53 (d, J = 7.5 Hz, 2H), 7.37 (t, J = 7.6 Hz, 2H), 7.29 (t, J = 7.3 Hz, 1H), 7.24-7.10 (m, 2H), 2.59 (s, 3H).…”
Section: -Methyl-3-(2-phenyl-4567-tetrahydro-1h-indol-3-yl)indolin-2one (8 A)mentioning
confidence: 99%